Incidence of internal marketing and organizational commitment in the retail sector - Canales Requena, Junior Alexis (2021)
The objective of this study was to determine the impact of internal marketing on the organizational commitment of employees in the retail sector. The method used was a quantitative correlational approach, at an explanatory level with a non-experimental design. The study sample consisted of 392 workers belonging to the retail sector. The results generated by structural equations show that specific relationships have p < 0.05, i.e. all the proposed hypotheses are accepted in the proposed correlation between internal marketing and the three types of organizational commitment, among them the affective commitment, which generates emotional ties between the employee and the organization, feeling proud to remain in the same linking the values and objectives of the same as their own goals, the commitment of permanence, which implies the risks involved in separating from the organization as well as the loss of all the benefits obtained and how these would be difficult to obtain if the employee were to leave the organization. Finally, the normative commitment, which arises when the employee perceives some kind of opportunity or special benefit in the organization, thus generating a bond of moral reciprocity, i.e. a bond of loyalty. The conclusion of the study is that the use of internal marketing for personnel selection is a fundamental tool for achieving acceptable levels of the three types of commitment mentioned above. This ensures the efficiency of the company both internally and externally, with long-term results.